Urban Mitigation Strategies: The Impact of Flood Control Devices on Reducing Environmental, Social, and Economic Damage - Costa , Michelle Nascimento; Carrara, Júlia Martins; Rocha, Cézar Henrique Barra (Technical and Scientific Journal Green Cities, 2025)
Flood containment devices are strategies that contribute to urban mitigation. Therefore, the general objective of the research is to analyze how the implementation of flood containment devices can influence environmental, social and economic issues. In view of the specific objectives we have: analyze the main types of flood containment devices used in urban areas and their characteristics; characterize technological innovations and changes in devices throughout history; compare case studies of different urban areas implementing flood containment devices, highlighting best practices and lessons learned. The work covers concepts and characterizes the different devices, with an approach related to technological innovations of best practices applied in different urban contexts, such as: the use of geosynthetics in dikes and dams; containment and detention basins; Sustainable Urban Drainage Systems (SuDS); sponge cities in line with the implementation of green roofs, swimming pool squares, floodable parks and permeable pavements. In parallel, a case study was developed on the city of Juiz de Fora and the containment devices adopted by the competent bodies to solve the problem. The methodology used is bibliographic and documentary, with a qualitative approach, in which articles published over a period of 10 years were used. Therefore, it is expected that through this work the gap in knowledge about the effectiveness of these technologies in mitigating urban impacts will be filled.